Outpatient prescription drug interactions at a city-affiliated healthcare center in Vietnam - Minh Cuong Nguyen; Dao Phuong Nguyen; Quang Loc Duyen Vo; Rebecca Susan Dewey; Minh Trung Nguyen; Quoc Quan Ly; Tu Nguyet Tran (Journal of Pharmacy & Pharmacognosy Research, 2024)
Context: Adverse drug interactions increase the risk of hospitalization, treatment costs, unfavorable treatment outcomes, and prolonged hospital stays. However, there are a limited number of studies conducted in city-affiliated healthcare settings in Vietnam.